L’identite Canadienne Française : Une Analyse De Les Anciens Canadiens De Philippe Aubert De Gaspé - Kalplata Kalplata (European Scientific Journal, ESJ, 2016)
Philippe Aubert de Gaspé establishes French Canadian identity through his book Les Anciens Canadiens written in 1863. This work announces already the start of nationalism in this part of the world, Canada, which is cold and isolated by its climate but where warmth and humanity are present in every heart. Les Anciens Canadiens is a book which is primarily Canadian. Through this novel, the author unveils Canadian characteristics, its local colour, its land and its language. In this article we discuss mainly the style used by the author which makes this book a Canadian book. This style comes from the environment, from the cold weather and the silence of Canada. We analyse also the character of José who represents the Canadian innocence. Like José, Canada is fresh, welcoming, kind, endowed with ancient tradition. He is witness to Canadian pride and love.